(untitled) (Bodhi Path, 2019)
Among the teachings of the Buddha compiled in the five collections of Pali Nikayas, we can find some very long discourses like ones in the Digha Nikaya. However, there can be some very short and condensed teachings found in the Dhammapada, which belongs to the Khuddaka Nikaya. There are 423 verses altogether in the Dhammapada. They were uttered by the Buddha on some 305 occasions for the benefit of various kinds of people during his life-long travels throughout different parts of ancient India. Every single verse of it is indeed a precious Gem of Wisdom in the Treasury of Truth since it conveys a message of deep meaning and also the very basic principles of the Dhamma, as we read in Verse 183 below: Not to do any evil, To cultivate good, To purify one’s mind, This is the Teachings of the Buddhas.